Prevalence of and risk factors for active tuberculosis in migrants screened before entry to the UK: a population-based cross-sectional study. Issue 8 (August 2016) - Aldridge, Robert W; Zenner, Dominik; White, Peter J; Muzyamba, Morris C; Loutet, Miranda; Dhavan, Poonam; Mosca, Davide; Hayward, Andrew C; Abubakar, Ibrahim
Summary: Background: An increasing number of countries with low incidence of tuberculosis have pre-entry screening programmes for migrants. We present the first estimates of the prevalence of and risk factors for tuberculosis in migrants from 15 high-incidence countries screened before entry to the UK. Methods: We did a population-based cross-sectional study of applicants for long-term visas who were screened for tuberculosis before entry to the UK in a pilot programme between Oct 1, 2005, and Dec 31, 2013. The primary outcome was prevalence of bacteriologically confirmed tuberculosis. We used Poisson regression to estimate crude prevalence and created a multivariable logistic regression model to identify risk factors for the primary outcome. Findings: 476 455 visa applicants were screened, and the crude prevalence of bacteriologically confirmed tuberculosis was 92 (95% CI 84–101) per 100 000 individuals. After adjustment for age and sex, factors that were strongly associated with an increased risk of bacteriologically confirmed disease at pre-entry screening were self-report of close or household contact with an individual with tuberculosis (odds ratio 11·6, 95% CI 7·0–19·3; p<0·0001) and being an applicant for settlement and dependant visas (1·3, 1·0–1·6; p=0·0203). Interpretation: Migrants reporting contact with an individual with tuberculosis had the highest risk of tuberculosis at pre-entry screening. To tackle this disease burden in migrants, a comprehensive and collaborative approach is needed between countries with pre-entry screening programmes, health services in the countries of origin and migration, national tuberculosis control programmes, and international public health bodies. Funding: Wellcome Trust, Medical Research Council, and UK National Institute for Health Research.